Growth Impairment in Acute Central Infectious Diseases - Bozzola, Mauro; Meazza, Cristina; Bossi, Grazia; Comoli, Patrizia; Bozzola, Elena (Journal of Pediatric Infectious Diseases, 2019)
Acute meningitis is an inflammation of the meninges affecting the pia, arachnoid, and subarachnoid space that still causes morbidity and mortality. Among the sequelae of meningitis, endocrine complications have been reported in patients recovering from acute central infectious diseases. Although the results of the studies are conflicting, the most common pituitary hormone deficiency during the acute phase or at 1-year follow-up evaluation is growth hormone deficiency, which results in growth impairment in children and a dysregulation of body composition and lipid metabolism throughout life. The mechanisms involved in growth failure secondary to meningitis are unknown. Therefore, endocrinological evaluation, including clinical, auxological, and hormonal assessments, should be performed during the acute phase of the infection and during recovery.
Keywords: growth; hypopituitarism; central infectious diseases